De la posture énonciative à la diathèse : gestion et gestation du sens - Marion Colas-Blaise (Corela)
This paper, which analyses extracts of Le balcon en forêt by Julien Gracq, aims to question once more the notion of enunciative posture that has been examined by Alain Rabatel in his point of view theory. Attention is focused on the posture of co-enunciation, which is approached from three different viewing angles: first, we reflect upon the notion of “recessive diathesis”, in relation to a centripetal force; second, we distinguish between tonic and low regimes of consensual and dissensual co-enunciation; third, we want to show that the posture of co-enunciation is based on a sensitive proto-posture, which underlies it.